A hydroprocessing catalyst for processing low sulfur feedstocks, its preparation and use

CN122912866APending Publication Date: 2026-10-16CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510408776.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-02
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

尽管硫化态活性相具有较高的加氢能力,但是其使用有一定的局限性:首先是为了维持催化活性的稳定,原料中和反应气氛中需要一定浓度的硫化氢来维持活性相的结构稳定性,因此,在处理越来越多的无硫或者低硫原料时,硫化态催化剂需要外加或者掺炼部分硫,造成应用范围受限

Benefits of technology

[0028]同现有技术相比,本发明方法所述的加氢处理催化剂能够处理低硫原料,具有高活性、稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912866A_ABST
    Figure CN122912866A_ABST
Patent Text Reader

Abstract

The application discloses a hydrogenation catalyst for treating low-sulfur raw materials and a preparation method and application thereof. The catalyst contains molybdenum metal, nickel metal and a metal additive, the metal additive being at least one or more of zinc, copper, magnesium and gallium, wherein, based on the weight of the catalyst, the mass content of the molybdenum element in the form of a single element is 4-20%, preferably 5%-18%, and further preferably 6%-16%, wherein the mass of +4 valence molybdenum accounts for 40%-95% of the total mass of molybdenum, preferably 45%-90%, and further preferably 50%-85%. The hydrogenation catalyst has good stability when treating low-sulfur raw materials compared with conventional noble metal and nickel catalysts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a hydrogenation catalyst for processing low-sulfur feedstocks, its preparation method, and its application; more specifically, it relates to a highly stable hydrogenation catalyst for processing low-sulfur feedstocks, its preparation method, and its application. Background Technology

[0002] Currently, distillate oil hydrotreating catalysts mainly use sulfide-formed Group VIB and VIII metals as the active phase. Although sulfide-formed active phases have high hydrotreating capacity, their use has certain limitations: First, to maintain the stability of catalytic activity, a certain concentration of hydrogen sulfide is required in the feedstock and reaction atmosphere to maintain the structural stability of the active phase. Therefore, when processing increasingly sulfur-free or low-sulfur feedstocks, sulfide-formed catalysts need to have some sulfur added or blended, limiting their application range. Second, sulfide-formed catalysts require sulfidation during start-up and regeneration after use, which is not only cumbersome but also causes significant environmental pollution. To solve these problems, researchers have attempted to prepare sulfur-free active phases for hydrotreating oil products.

[0003] CN112742478A discloses a method for preparing a hydrogenation catalyst. This catalyst contains an organomolybdenum compound and an organoferric salt arranged in a specific chemical formula as the active phase. This catalyst exhibits good hydrogenation performance, ring-opening activity, and denitrification effect while possessing high metal content and low cost. However, this catalyst has poor stability and deactivates rapidly under high-temperature conditions.

[0004] CN1146164A discloses a catalyst with nickel and zirconium as active components and silicon-aluminum as a support, used in the preparation of medical white oil, high-purity medical paraffin, and mixtures of hydrocarbons with low boiling points and low or no aromatic content. However, this catalyst is less effective when processing petroleum fractions with high aromatic content.

[0005] CN103071509A discloses a hydrogenation catalyst. It uses nickel and zinc as active components, manganese oxide and molybdenum oxide as promoters, and potassium oxide, magnesium oxide, and calcium oxide as auxiliary agents. This catalyst has the advantages of low hydrogen consumption and ease of start-up. However, its stability is relatively poor, making it unsuitable for long-term, high-temperature operation.

[0006] CN101157056A discloses a hydrogenation catalyst, wherein the support material is Al2O3, SiO2, TiO2, or a composite oxide of two thereof prepared by a sol-gel method. A nickel- and cobalt-containing salt solution is introduced during the sol-gel preparation of the support material. The catalyst of this invention exhibits excellent hydrodesulfurization and hydrodenitrogenation activity. However, when processing high-aromatic feedstocks, the catalyst's hydrogenation activity is slightly insufficient.

[0007] In existing technologies, the active component of hydrogenation catalysts is generally a metal sulfide, which usually needs to be pre-sulfurized, especially when processing low-sulfur feedstock oil. In order to maintain hydrogenation activity, sulfur replenishment is required. Summary of the Invention

[0008] To address the shortcomings of existing technologies, this invention provides a hydrogenation catalyst for processing low-sulfur feedstocks, its preparation method, and its applications. The hydrogenation catalyst exhibits better stability compared to conventional noble metal and nickel-based catalysts when processing low-sulfur feedstocks.

[0009] The first aspect of the present invention provides a hydrogenation catalyst for processing low-sulfur feedstock, the catalyst containing molybdenum metal, nickel metal and a metal additive, wherein the metal additive is at least one or more of zinc, copper, magnesium and gallium, wherein, based on the weight of the catalyst, the mass content of molybdenum element as elemental is 4-20%, preferably 5%-18%, more preferably 6%-16%, wherein the mass of +4 valence molybdenum accounts for 40%-95% of the total mass of molybdenum, preferably 45%-90%, more preferably 50%-85%.

[0010] In the hydrogenation catalyst of the present invention, the mass of nickel element is 1.0%-6.0% based on elemental mass, preferably 1.5%-5.5%, and more preferably 2.0%-5.0%.

[0011] In the hydrogenation catalyst of the present invention, the mass of the auxiliary metal, calculated as elemental, is 0.1-3.0%, preferably 0.2%-2.5%, and more preferably 0.3-2.0%.

[0012] In the hydrogenation catalyst of the present invention, the catalyst, when observed under TEM, contains an active phase (Mo species) with alternating light and dark stripes, the stripe spacing being 0.3-0.4 nm, and the long axis of the active phase being 2.0-12.0 nm, preferably 3.0-10.0 nm.

[0013] In the hydrogenation catalyst of the present invention, the hydrogenation catalyst contains a support, which can be one or more of alumina, amorphous silica-alumina, macroporous silica, and titanium-silicon composite materials, preferably γ-alumina. Based on the weight of the final hydrogenation catalyst, the support mass content is 50%-90%, preferably 60%-85%, and more preferably 65%-80%.

[0014] In the hydrogenation catalyst of this invention, the support may be doped with a small amount of one or more heteroatoms such as silicon, phosphorus, boron, magnesium, and fluorine to improve the support performance. The amount of heteroatoms incorporated shall not exceed 5.0% of the total mass of the support, preferably 0-4.0%. The heteroatoms may be incorporated in a manner that is already known, either during the preparation of the support or after the support is prepared.

[0015] In the hydrogenation catalyst of this invention, the support should have the following properties: a pore volume of 0.6~1.3 cm³. 3 / g, with a preferred pore volume of 0.7~1.2 cm³. 3 / g, specific surface area is 180-340m² 2 / g, preferably 210-310 m 2 / g.

[0016] A second aspect of the present invention provides a method for preparing a hydrogenation catalyst for processing low-sulfur feedstock, the method comprising the following steps: (3) Select or prepare a hydrogenation catalyst support. (4) Introducing metallic molybdenum onto the carrier in step (1); (3) Step (2) Introducing organonickel onto the inorganic refractory oxide carrier of metallic molybdenum The final hydrogenation catalyst is prepared by drying and reducing the catalyst with organometallic additives.

[0017] Furthermore, the carrier in step (1) can be a commercially available product or prepared according to existing technology.

[0018] Furthermore, the introduction of metallic molybdenum in step (2) can be achieved through conventional impregnation. After introduction, it can be dried at a temperature of 100-180°C, preferably 120-160°C, for a time of 2-20 hours, preferably 4-16 hours. After drying, it can be calcined at a temperature of 380-600°C, preferably 400-550°C, for a time of 2-12 hours, preferably 3-10 hours.

[0019] Furthermore, after introducing metallic molybdenum in step (2), the form of metallic molybdenum on the carrier can be molybdenum salt, molybdenum oxide, or elemental molybdenum.

[0020] Further, in step (3), the organic groups corresponding to the organonickel and organometallic additives are organic acid radicals or organic complexes. The organic acid radicals are one or more of malonate, citrate, oxalate, ethylenediaminetetramethylenephosphonate, salicylate, benzoate, and tartrate. The organic complexes are one or more of acetylacetone, EDTA, and NTA. The organic acid radicals or organic complexes corresponding to the organonickel and organometallic additives can be the same or different; preferably, the same organic acid radical or organic complex is used.

[0021] Furthermore, in step (3), organonickel and organometallic additives can be introduced separately or simultaneously onto the carrier on which molybdenum is introduced, preferably simultaneously; more preferably, when they are introduced simultaneously, the organonickel and organometallic additives correspond to the same organic acid anion or organic complex.

[0022] Furthermore, in step (3), the organonickel and organometallic additives are introduced using an impregnation method, which can be either stepwise impregnation or co-impregnation, with co-impregnation being preferred. The solvent used can be one or more of water, ethanol, acetone, and toluene. During the co-impregnation process, the molar concentration of the organonickel, calculated as nickel, is 0.1-2.0 mol / L, preferably 0.2-1.5 mol / L, and the molar concentration of the organometallic additive, calculated as a metal additive, is 0.05-1.0 mol / L, preferably 0.1-0.5 mol / L. The impregnation can be performed multiple times as needed.

[0023] Further, in step (3), based on the weight of the final hydrogenation catalyst, the mass content of the introduced organic acid anions and / or organic complexes is 2.0%-25.0%, preferably 3.0%-23.0%, and more preferably 4.0%-20.0%.

[0024] Further, in step (3), the drying temperature is 80-180℃, preferably 100-160℃, and the drying time is 1-10 hours, preferably 2-8 hours. The hydrogen reduction temperature is 150-500℃, preferably 250-400℃, the reduction pressure is 2.0-16.0MPa, preferably 4.0-14.0MPa, and the hydrogen flow rate is 2.0-30 Nml / min·g. 催化剂 The preferred concentration is 4.0-20 Nml / min·g. 催化剂 The hydrogen treatment time is 2-30 hours, preferably 4-28 hours.

[0025] The third aspect of the present invention provides a method for hydrogenating low-sulfur biomass feedstock oil, which uses the above-mentioned hydrogenation catalyst to introduce low-sulfur feedstock oil into the reduced hydrogenation catalyst to carry out the hydrogenation reaction.

[0026] Furthermore, the low-sulfur feedstock oil is a feedstock with a sulfur content between 0 and 5000 ppm.

[0027] Furthermore, the hydrogenation reaction conditions are as follows: reaction temperature 200-400℃, preferably 220-380℃; hydrogen pressure 2.0-18.0 MPa, preferably 4.0-16.0 MPa; and liquid hourly space velocity 0.2-3.0 h⁻¹. -1 Preferably 0.3-2.0 h -1 The hydrogen-to-oil ratio is 100:1-1500:1, preferably 300:1-1200:1.

[0028] Compared with the prior art, the hydrogenation catalyst described in the method of the present invention can process low-sulfur feedstocks and has high activity and stability.

[0029] Instruction manual illustrations Figure 1The image shows a TEM image of the catalyst in Example 1, with the striped structure within the red box. Detailed Implementation

[0030] The present invention will be further described below with reference to the embodiments, but the following embodiments do not constitute a limitation of the present invention. Unless otherwise specified, the percentage content of the materials mentioned herein is a mass percentage content.

[0031] Weigh 6000.0 g of alumina dry adhesive powder, add 200.0 g of acetic acid, 300.0 g of citric acid, 400.0 g of polyethylene glycol, 200.0 g of urea, 300.0 g of guar gum powder, and 100.0 g of cellulose. Mix thoroughly, then add 4000.0 g of an aqueous solution containing 1.0% nitric acid. Knead for 20.0 min, then extrude into strips using a 3.0 mm diameter four-leaf clover-shaped perforated plate. Dry at 120°C for 6.0 h and calcine at 650°C for 6.0 h. The resulting carrier is denoted as S-0.

[0032] The pore properties of the S-0 carrier were determined as follows: specific surface area of ​​224 m². 2 / g, pore volume 1.19 cm³ 3 / g.

[0033] A specific method for determining the content of +4 valent molybdenum is provided. The valence state of molybdenum was measured using XPS with a Thermo Fisher ESCALAB Xi X-ray photoelectron spectrometer. During the test, the 3d... 5 / 2 Molybdenum with orbitals between 229 and 230 eV can be classified as +4 valence molybdenum.

[0034] The specific TEM measurement method used a Tecnai G2-F20 high-resolution transmission electron microscope to analyze the microstructure of the catalyst, with an accelerating voltage of 200 kV.

[0035] Example 1 Weigh 15.0 g of ammonium heptamolybdate tetrahydrate, dissolve it in 100 ml of deionized water, and prepare a solution labeled MQ-1.

[0036] Weigh 100.0 g of carrier S-0, impregnate S-0 with MQ-1, and dry at 120°C for 6.0 hours. The resulting intermediate is denoted as M-1.

[0037] Weigh 10.0 g nickel tartrate, 3.0 g copper tartrate, and 3.0 g tartaric acid, dissolve them in deionized water, and bring the volume to 90 ml. The resulting impregnation solution is designated as NQ-1.

[0038] M-1 was impregnated with NQ-1, dried at 120°C for 6.0 hours, and then reduced under hydrogen atmosphere at a reaction temperature of 320°C, a reduction pressure of 8.0 MPa, and a hydrogen flow rate of 10.0 Nml / min·g. 催化剂 After hydrogen treatment for 5.0 hours, the resulting catalyst is designated Cat-1.

[0039] Example 2 Weigh 20.0 g of ammonium heptamolybdate tetrahydrate, dissolve it in 100 ml of deionized water, and prepare a solution labeled MQ-2.

[0040] Weigh 100.0 g of carrier S-0, impregnate S-0 with MQ-1, and dry at 120°C for 6.0 hours. The resulting intermediate is denoted as M-2.

[0041] Weigh 15.0 g of nickel acetylacetone and 5.0 g of copper acetylacetone, dissolve them in a 1:1 mixture of deionized water and ethanol, and bring the volume to 120 ml. The resulting impregnation solution is designated as NQ-2.

[0042] M-2 was impregnated with NQ-2, dried at 120°C for 6.0 hours, and then reduced under hydrogen atmosphere at a reaction temperature of 320°C, a reduction pressure of 8.0 MPa, and a hydrogen flow rate of 10.0 Nml / min·g. 催化剂 After hydrogen treatment for 5.0 hours, the resulting catalyst is designated Cat-2.

[0043] Example 3 Weigh 30.0 g of ammonium heptamolybdate tetrahydrate and 20.0 g of ammonia solution with a mass fraction of 20%, dissolve them in 120 ml of deionized water, and prepare a solution labeled MQ-3.

[0044] Weigh 100.0 g of carrier S-0, impregnate S-0 with MQ-3, and dry at 120°C for 6.0 hours. The resulting intermediate is denoted as M-3.

[0045] Weigh 15.0 g of nickel citrate, 5.0 g of zinc citrate, and 12.0 g of citric acid, dissolve them in deionized water, and bring the volume to 120 ml. The resulting impregnation solution is labeled NQ-3.

[0046] M-3 was impregnated with NQ-3, dried at 120°C for 6.0 hours, and then reduced under hydrogen atmosphere at a reaction temperature of 320°C, a reduction pressure of 8.0 MPa, and a hydrogen flow rate of 10.0 Nml / min·g. 催化剂 After hydrogen treatment for 5.0 hours, the resulting catalyst is designated Cat-3.

[0047] Example 4 Weigh 35.0 g of ammonium heptamolybdate tetrahydrate and 20.0 g of ammonia solution with a mass fraction of 20%, dissolve them in 120 ml of deionized water, and prepare a solution labeled MQ-4.

[0048] Weigh 100.0 g of carrier S-0, impregnate S-0 with MQ-4, and dry at 120°C for 6.0 hours. The resulting intermediate is denoted as M-4.

[0049] Weigh 18.0 g of nickel glycolate and 13.0 g of zinc gluconate, dissolve them in deionized water, and make up to 120 ml to obtain the impregnation solution, which is designated as NQ-4.

[0050] M-4 was impregnated with NQ-4, dried at 120°C for 6.0 hours, and then reduced under hydrogen atmosphere at a reaction temperature of 320°C, a reduction pressure of 8.0 MPa, and a hydrogen flow rate of 10.0 Nml / min·g. 催化剂 After hydrogen treatment for 5.0 hours, the resulting catalyst was designated Cat-4.

[0051] Comparative Example 1 The preparation of impregnation solution MQ-3 and intermediate M-3 is the same as in Example 3.

[0052] Weigh 23.0 g of nickel nitrate hexahydrate and 12.0 g of citric acid, dissolve them in deionized water, and bring the volume to 110 ml. The resulting impregnation solution is labeled DQ-1.

[0053] M-3 was impregnated with DQ-1, dried at 120°C for 6.0 hours, and then reduced under hydrogen atmosphere at a reaction temperature of 320°C, a reduction pressure of 8.0 MPa, and a hydrogen flow rate of 10.0 Nml / min·g. 催化剂 After hydrogen treatment for 5.0 hours, the resulting catalyst was designated DCT-1.

[0054] Comparative Example 2 The preparation of intermediate M-3 is the same as in Example 3.

[0055] Weigh 23.0 g nickel nitrate, 8.0 g zinc nitrate, and 12.0 g citric acid, dissolve them in deionized water, and bring the volume to 110 ml. The resulting impregnation solution is labeled DQ-2.

[0056] M-3 was impregnated with DQ-2, dried at 120°C for 6.0 hours, and then reduced under hydrogen atmosphere at a reaction temperature of 320°C, a reduction pressure of 8.0 MPa, and a hydrogen flow rate of 10.0 Nml / min·g. 催化剂 After hydrogen treatment for 5.0 hours, the resulting catalyst was designated DCT-2.

[0057] Comparative Example 3 The preparation of intermediate M-3 is the same as in Example 3.

[0058] Weigh 23.0 g of nickel nitrate hexahydrate, 5.0 g of zinc citrate, and 12.0 g of citric acid, dissolve them in deionized water, and bring the volume to 110 ml. The resulting impregnation solution is labeled DQ-3.

[0059] M-3 was impregnated with DQ-3, dried at 120°C for 6.0 hours, and then reduced under hydrogen atmosphere at a reaction temperature of 320°C, a reduction pressure of 8.0 MPa, and a hydrogen flow rate of 10.0 Nml / min·g. 催化剂 After hydrogen treatment for 5.0 hours, the resulting catalyst was designated DCT-3.

[0060] Table 2 Catalyst Composition Catalyst number Mo element m% Ni content m% Metallic types Oxygen content m% Cat-1 9.6 2.5 copper 0.8 Cat-2 11.5 3.7 copper 1.0 Cat-3 13.3 3.8 Zinc 1.3 Cat-4 15.0 4.0 Zinc 1.4 DCT-1 13.5 3.9 - - DCT-2 13.5 3.9 Zinc 1.4 DCT-3 13.4 3.8 Zinc 1.3 Table 3 Determination of Organic Matter Content in Catalyst Intermediates Intermediate number Organic matter content, m% TM-1 9.0 TM-2 10.0 TM-3 15.8 TM-4 14.4 DTM-1 7.2 DTM-2 7.0 DTM-3 8.9 The proportion of molybdenum in the Mo+4 valence state was analyzed in catalysts Cat-1, Cat-2, Cat-3, Cat-4, DCT-1, DCT-2, and DCT-3, and the results are shown in Table 4.

[0061] Table 4. Proportion of Mo+4 valence molybdenum in the catalyst Catalyst number The proportion of +4 valent molybdenum Cat-1 60.2 Cat-2 61.7 Cat-3 62.7 Cat-4 59.8 DCT-1 26.1 DCT-2 31.7 DCT-3 33.4 Catalysts Cat-1, Cat-2, Cat-3, Cat-4, DCT-1, DCT-2, DCT-3, and DCT-4 were characterized by TEM, and the results are shown in Table 5.

[0062] Table 5 Catalyst TEM Data Table 5 Catalyst TEM Data Catalyst number The average length of the stripes with a spacing of 0.3–0.4 nm is in nm. Cat-1 8.6 Cat-2 7.3 Cat-3 9.1 Cat-4 8.5 DCT-1 37.4 DCT-2 24.4 DCT-3 24.8 Examples 5-8 Cat-1, Cat-2, Cat-3, and Cat-4 were placed in a reaction tube, and recycled kitchen waste oil (properties of which are shown in Table 6) was introduced into the reaction tube. The reaction pressure was set to 10.0 MPa, the reaction temperature was controlled at 300℃, and the liquid hourly space velocity was 0.6 h⁻¹. -1 The hydrogen-to-oil ratio was 400:1. After 600 hours of reaction, the composition and properties of the sample were analyzed, and the results are shown in Table 7.

[0063] Comparative Examples 4-6 DCT-1, DCT-2, and DCT-3 were placed in a reaction tube, and recycled kitchen waste oil (properties shown in Table 5) was introduced into the reaction tube. The reaction pressure was set to 10.0 MPa, the reaction temperature was controlled at 300℃, and the liquid hourly space velocity was 0.6 h⁻¹. -1 The hydrogen-to-oil ratio was 400:1. After 600 hours of reaction, the composition and properties of the sample were analyzed, and the results are shown in Table 6. Table 6: Property Analysis of Recycled Kitchen Waste Oil Source of raw materials Recycling waste cooking oil Density (20℃), kg / m3 0.912 Pour point, ℃ 39 Sulfur content, ng / μl 26.3 Nitrogen content, ng / μl 54.1 Chlorine content, mg / kg 8.71 Phosphorus content, mg / kg 27.91 Oxygen content, m% 13.61 Carbon content, m% 75.17 Hydrogen content, m% 12.69 Acid value (mgKOH / g) 159.60 Residual charcoal, m% 0.73 Table 7. Evaluation results of catalysts in the examples and comparative examples. Experiment number Catalyst number Nitrogen content ng / μl Oxygen content, m% Acid value (mgKOH / g) Example 5 CAT-1 2.3 1.86 1.15 Example 6 CAT-2 1.8 1.44 0.91 Example 7 CAT-3 <1 1.28 0.79 Example 8 CAT-4 <1 0.90 0.62 Comparative Example 4 DCT-1 10.5 5.81 10.85 Comparative Example 5 DCT-2 4.9 3.15 6.69 Comparative Example 6 DCT-3 8.7 5.20 7.94 The evaluation results show that the catalyst provided by this invention has good hydrodeoxygenation and hydroacidification activity when processing high-oxygen and high-acid-value raw materials.

Claims

1. A hydrogenation catalyst for processing low-sulfur feedstock, characterized in that: The catalyst contains molybdenum metal, nickel metal, and a metal additive, wherein the metal additive is at least one or more of zinc, copper, magnesium, and gallium. Based on the weight of the catalyst, the mass content of molybdenum as elemental molybdenum is 4-20%, preferably 5%-18%, more preferably 6%-16%, wherein the mass of +4 valence molybdenum accounts for 40%-95% of the total mass of molybdenum, preferably 45%-90%, more preferably 50%-85%.

2. The method according to claim 1, characterized in that: Based on the weight of the final catalyst, the nickel content, expressed as elemental, is 1.0%-6.0%, preferably 1.5%-5.5%, and more preferably 2.0%-5.0%.

3. The method according to claim 1, characterized in that: Based on the weight of the final catalyst, the mass of the auxiliary metal, expressed as an element, is 0.1-3.0%, preferably 0.2%-2.5%, and more preferably 0.3-2.0%.

4. The method according to claim 1, characterized in that: The catalyst contains an active phase with alternating light and dark stripes, the stripe spacing being 0.3-0.4 nm, and the long axis of the active phase being 2.0-12.0 nm, preferably 3.0-10.0 nm.

5. A method for preparing a hydrogenation catalyst for processing low-sulfur feedstock, characterized in that the method includes the following steps: (1) Select or prepare a hydrogenation catalyst support, (2) Introducing metallic molybdenum onto the carrier in step (1); (3) Step (2) Introducing organonickel onto the inorganic refractory oxide carrier of metallic molybdenum The final hydrogenation catalyst is prepared by drying and reducing the catalyst with organometallic additives.

6. The method according to claim 5, characterized in that: After the metal is introduced in step (2), it is dried at a temperature of 100-180℃, preferably 120-160℃, and for a time of 2-20 hours, preferably 4-16 hours.

7. The method according to claim 6, characterized in that: After drying, the product is calcined at a temperature of 380-600℃, preferably 400-550℃, for a time of 2-12 hours, preferably 3-10 hours.

8. The method according to claim 5, characterized in that: After the introduction of metallic molybdenum in step (2), the metallic molybdenum on the carrier is in the form of molybdenum salt, molybdenum oxide, or elemental molybdenum.

9. The method according to claim 5, characterized in that: In step (3), the organic groups corresponding to the organonitrile and organometallic additives are organic acid radicals or organic complexes. The organic acid radicals are one or more of malonate, citrate, oxalate, ethylenediaminetetramethylenephosphonate, salicylate, benzoate, and tartrate. The organic complexes are one or more of acetylacetone, EDTA, and NTA.

10. The method according to claim 9, characterized in that: The organic acid radicals or organic complexes corresponding to organonickel and organometallic additives may be the same or different, and it is preferred to use the same organic acid radicals or organic complexes.

11. The method according to claim 5, characterized in that: In step (3), organonickel and organometallic additives are introduced separately or simultaneously onto the carrier on which metallic molybdenum is introduced, preferably simultaneously; more preferably, when they are introduced simultaneously, the organonickel and organometallic additives correspond to the same organic acid anion or organic complex.

12. The method according to claim 5, characterized in that: In step (3), based on the weight of the final hydrogenation catalyst, the mass content of the introduced organic acid anions and / or organic complexes is 2.0%-25.0%, preferably 3.0%-23.0%, and more preferably 4.0%-20.0%.

13. The method according to claim 5, characterized in that: In step (3), the drying temperature is 80-180℃, preferably 100-160℃, and the drying time is 1-10 hours, preferably 2-8 hours.

14. The method according to claim 5, characterized in that: In step (3), the hydrogen reduction temperature is 150-500℃, preferably 250-400℃, the reduction pressure is 2.0-16.0MPa, preferably 4.0-14.0MPa, and the hydrogen flow rate is 2.0-30 Nml / min·g. 催化剂 The preferred concentration is 4.0-20 Nml / min·g. 催化剂 The hydrogen treatment time is 2-30 hours, preferably 4-28 hours.

15. A method for hydrogenating low-sulfur biomass feedstock oil, characterized in that: Using any one of the hydrogenation catalysts of claims 1-4, a low-sulfur feedstock is introduced into the reduced hydrogenation catalyst to carry out the hydrogenation reaction.

16. The method according to claim 15, characterized in that: The low-sulfur feedstock oil is a feedstock with a sulfur content between 0 and 5000 ppm.

17. The method according to claim 15, characterized in that: The hydrogenation reaction conditions are as follows: reaction temperature 200-400℃, preferably 220-380℃; hydrogen pressure 2.0-18.0 MPa, preferably 4.0-16.0 MPa; and liquid hourly space velocity (LISH) 0.2-3.0 h⁻¹. -1 Preferably 0.3-2.0 h -1 The hydrogen-to-oil ratio is 100:1-1500:1, preferably 300:1-1200:1.

Citation Information

Patent Citations

  • Hydrogenation catalysts carrier with nickel and cobalt, hydro-catalyst and its preparing method

    CN101157056A

  • Hydrogenation catalyst and application thereof

    CN103071509A

  • Preparation method of hydrogenation catalyst, hydrogenation catalyst and application of hydrogenation catalyst

    CN112742478A